Ultrasonic a testing of honeycomb composite specimens - Ramamoorthy, Jeyasri (Nanyang Technological University, 2022)
Composite honeycombs have desirable strength-to-weight ratio and heat insulation properties due to their unique geometry consisting of a honeycomb core that is sandwiched between two face sheets. However, the structure also has defects that require reliable Non-Destructive Testing methods, like Ultrasonic Testing, for defect detection. Ultrasonic Testing involves transmitting sound waves that get reflected upon encountering a discontinuity within any material. The strength of the reflected signals can then be easily analysed to characterize flaws. Currently, Through Transmission, which requires two probes, is prevalent in the Ultrasonic Testing of composite honeycombs. This is however complex and it is thus necessary to identify flaws that Pulse Echo using a single probe can detect. In this final project work, Ultrasonic A-Scan was used to investigate the detection of defects such as fiber delaminations, cuts in the honeycomb core, and skin to core disbonds found within composite honeycomb structures. The specimens used for testing were first fabricated with either Nomex or Aluminium for the honeycomb core and Carbon Fiber Reinforced Polymer for the face sheets, with the aforementioned defects incorporated at various depths. The testing was then done using both the Pulse Echo and Through Transmission techniques, where the probe frequency was also varied. Via the experiments, it was discovered that Through Transmission still performs better than the Pulse Echo technique in detecting all the different types of defects. Pulse Echo is limited to only detecting defects close to the probe surface and is rendered useless when the defect is extremely far from the probe, such as when the probe is on the opposite side of the defect. The material of the honeycomb core and probe frequency were also found to have a noticeable impact on the quality of the signals and consequently the capabilities of Ultrasonic Testing in finding the defects within the composite honeycomb specimens.